The Use of the Ultrasonic Sensor as a Potential Teaching Tool in the Teaching-Learning Process of Simple Harmonic Motion in High School - M. Filho, Elson A. U.; S., José P. Da; Lima, João P. R. De; Rossiter, Sarah T. De S.; Costa, Fabio A. S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
The following study highlights the increasing necessity of experimental classes with a significant focus on robotics, especially in the study of vibrations and simple harmonic motion (SHM). The students' perception that abstract subjects become more comprehensible with the use of empirical resources and robotic solutions is evident. However, acquiring measurement equipment is often unfeasible due to its high cost. To surpass this obstacle, the utilization of an Arduino prototyping platform and ultrasound sensors was proposed, integrating robotics into the teaching of SHM. The results indicated that the prototype developed with robotic components has the potential to generate greater dynamism and appeal in the classes, beyond its easy setup, presentation, and low cost. This study contributes to the promotion of more practical and accessible teaching approaches, highlighting robotics as an essential tool to overcome the barriers related to access to experimental equipment.